Crime and criminals - Fisanick, Christina (Opposing viewpoints series, 2010)
Prisoners have too many rights / Jack Lee -- Prisoners need more rights / Commission on Safety and Abuse in America's Prisons -- Men suffer more discrimination by the judicial system than women / Richard F. Doyle -- Women suffer more discrimination by the judicial system than men / Correctional Association of New York -- Women in prison are sexually vulnerable / Nicole Summer -- Men in prison are sexually vulnerable / Daniel Brook -- Minorities are unfairly targeted by law enforcement / Leadership Conference on Civil Rights Education Fund -- Minorities are not unfairly targeted by law enforcement / New Century Foundation -- Older prisoners should be released early / Justice Matters -- Older prisoners should not receive lenient sentences / Kelly Porcella -- Mentally ill offenders should be held responsible for their actions / Richard E. Vatz -- Mentally ill offenders should not be executed / American Civil Liberties Union -- White-collar criminals should be given lighter sentences / Rob Norton -- White-collar criminals should not be released early / Ming Zhen Shakya -- The death penalty deters crime / David B. Muhlhausen -- The death penalty does not deter crime / Aundre M. Herron -- Surveillance equipment helps reduce crime / Spencer E. Ante -- Surveillance equipment does not reduce crime / American Civil Liberties Union -- Tougher sentences deter crime / John Lott -- Tougher sentences do not deter crime / The JFA Institute -- Measuring recidivism is complicated / Martha Lyman and Stefan LoBuglio -- Rehabilitation reduces recidivism rates among drug offenders / Government Accountability Office -- Corrections officials should be held responsible for recidivism / Jason Newman -- Restorative justice is more effective than retribution in preventing recidivism / Jonathan Aitken -- Transition programs reduce recidivism rates / Danny L. Jordan -- Relapse prevention therapy can lower recidivism rates / George A. Parks